Integration of emergency management and business continuity: case study - assessing your organization's resiliency - Di Giambattista, Gian (Henry Stewart Talks, 2011)
OPG profile, Emergency management / business continuity, OPG's emergency management program, CSA Z1600 overview, Incident management system doctrine overview, Gap assessment methodology, Ratings for CSA Z1600 and IMS doctrine, Maturity scorecard based on CSA Z1600, The maturity model, OPG maturity scorecard, Different aspects of maturity scorecard, EM/BC-pandemic plan example, Assessing the pandemic plan